Pengaruh Penggunaan E-commerce Shopee Terhadap Perilaku Belanja Online Mahasiswa Kota Pekanbaru - Arif Fathurrahman Nurza; Rina Susanti Susanti (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The study seeks to examine students’ shopping behaviours on shopee and evaluate their impact through Jean Paul Baudrillard consumer society theory. Quantitative research methods are used with inferential statistical analysis. The study was located at the Fakultas Ekonomi dan Bisnis Universitas Riau. Data collection using questionnaires, observation, and documentation. The population of the study were undergraduate students of the Fakultas Ekonomi dan Bisnis Universitas Riau who used e-commerce shopee. The research sample consisted of 96 students. Sampling was conducted using purposive sampling, requiring participants to possess an active shopee account and to have utilised shopee for shopping consistently over the preceding four months. A basic regression test was employed for data analysis. The study’s findings suggest that pictures, symbols, simulations, simulacra, and hyperreality intrinsically drive students’ online purchasing behaviours driven by desire. The results of the data analysis indicate that Ha is accepted, which signifies an influence of shopee’s e-commerce on students’ online buying behaviours, as evidenced by a significance value of less than 0.10 (0.001 < 0.10).